Bahan Ajar Berbasis Science, Technology, Engineering, And Mathematics (STEM) Untuk Meningkatkan HOTS Siswa Kelas III Sekolah Dasar - Marsari, Henni; Rifma, Rifma (Universitas PGRI Madiun, 2023)
Higher-order thinking skills in the current context as abilities that promote deeper conceptual understanding based on Bloom's taxonomy. The purpose of this study was to obtain data on STEM-based teaching materials to improve HOTS for third grade elementary school students. This type of research is development research using the ADDIE development model. Analysis of teaching material validation data by educational experts and practitioners yielded an average of 91.7. The usability test results obtained an average of 91. The effectiveness of teaching materials was also shown by increasing HOTS students after using STEM 87. Based on these results, it can be concluded that STEM teaching materials developed for class III elementary schools were considered very effective, very practical, and effective for improve the HOTS of grade III elementary school students